The Effect of Special Autonomy Fund Allocation for Education and Health on Human Development in Aceh Province, Indonesia - Yulianti, Reka; Syahnur, Sofyan; Abrar, Muhammad; Srinita, Srinita (Graha Primera Saintifika, 2024)
Aceh is one of the three provinces in Indonesia that receive special autonomy funds, which function as a stimulant to accelerate development. This study aims to analyze the effect of these funds in education and health on human development in Aceh Province. It uses secondary data obtained from Bappeda Aceh Province and the Statistics of Aceh Province. The type of data used is panel data, with the cross-section consisting of 23 districts/cities in Aceh Province and the time series spanning from 2011 to 2022. Panel data regression and Moderated Regression Analysis (MRA) methods were employed to analyze the data and achieve the research objectives. The findings of this study indicate that special autonomy funds for education have a significant positive effect on the Human Development Index (HDI), while special autonomy funds for health have a significant negative effect on HDI in Aceh Province. Additionally, economic growth does not moderate the effect of special autonomy funds in education and health on HDI in Aceh Province. It is recommended that the Aceh Provincial Government implement more intensive policies, such as monitoring and evaluating the progress of education and health programs, and involving community participation in these programs to achieve optimal targets.